Effect of workload history on vigilance performance. - Cox-fuenzalida, Luz-eugenia. (My University, 2000)
Effects of sudden transitions in workload level on performance indices were investigated within the newly emerging paradigm of workload history. It has been previously reported that a sudden decrease in workload level results in a significant immediate decrement in performance (Cumming & Croft, 1973; Goldberg & Stewart, 1980; Matthews, 1986). Study 1 consisted of 198 participants who completed a protocol of training, baseline and test trials designed to examine the effects of workload history on performance. Specifically, this study tested for the reported general decrement in performance and investigated the nature of the decrement. Results indicated that a sudden decrease in workload level results in an immediate significant decrement in response time, total errors, etc., while a sudden increase fails to result in the same immediate decrement. This study reports new findings, i.e., either a sudden increase or decrease could lead to a loss in accuracy and a slowing of response time in a longer time course. An explanation of the decrement is offered in terms of a resource adaptation-depletion model. Study 2 tested whether time on task or fatigue might have been responsible for the decrement in performance following sudden transitions in workload (reported in Study 1). No significant results were found; therefore, it appears that the decrement in performance following workload transitions is a result of something inherent in the workload shift rather than an effect of time on task or fatigue.
Keywords: Employees Workload Psychological aspects.; Psychology, Industrial.; Psychology, Experimental.